A Network Design Using MPLS For Video Streaming Services - Mulyanita Br Damanik; Solly Aryza; Yoffi Andinata (Sean Institute, 2024)
The design of a reliable and efficient network is crucial to support services that require large data transfers, such as video streaming. This research aims to design a network using Multiprotocol Label Switching (MPLS) technology to enhance the quality of video streaming services. MPLS is known as an effective solution for managing network traffic due to its ability to perform label-based routing, which allows for more optimal and faster path selection compared to traditional routing methods. In this study, the MPLS network design is implemented to provide better Quality of Service (QoS), focusing on parameters such as latency, jitter, and packet loss, which greatly impact the user experience in video streaming. The design method involves selecting the most efficient routes and managing priority traffic to ensure that video streaming data can be transmitted with optimal speed and stability. The results of this study show that the use of MPLS in networks for video streaming services can improve bandwidth efficiency, reduce disruptions caused by network congestion, and ensure more stable playback with minimal buffering. Therefore, MPLS-based network design becomes an effective solution to support higher-quality video streaming services.